1999
DOI: 10.1046/j.1365-2249.1999.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Th1 responses driven by IL-12 are associated with enhanced expression of CD40 ligand

Abstract: SUMMARYIL-12 is the prominent inducer of Th1 responses in humans and in the mouse. CD40 ligand (CD40L) plays important roles in regulation of immune responses, including T cell-dependent activation of B cells and cytokine production by monocytes and dendritic cells. The present study examined the in¯uences of IL-12 on the CD40L expression of activated human CD4T cells. IL-12 enhanced CD40L expression on CD4T cells stimulated with immobilized anti-CD3 in the complete absence of accessory cells, whereas IL-4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…It has been shown that NK cells express CD40L (26) and can be activated to kill CD40-expressing tumors in vitro (26). Therefore, it is possible that increased production of IL-12 by activated APC can up-regulate expression of CD40L on NK cells in a similar way as was reported for CD4 ϩ T cells (29). Consequently, those activated NK cells may kill tumor cells via CD40-CD40L interaction.…”
Section: Discussionmentioning
confidence: 63%
“…It has been shown that NK cells express CD40L (26) and can be activated to kill CD40-expressing tumors in vitro (26). Therefore, it is possible that increased production of IL-12 by activated APC can up-regulate expression of CD40L on NK cells in a similar way as was reported for CD4 ϩ T cells (29). Consequently, those activated NK cells may kill tumor cells via CD40-CD40L interaction.…”
Section: Discussionmentioning
confidence: 63%
“…21 T cells were obtained from the treated cell population by rosetting with neuraminidasetreated sheep red blood cells, as previously described. 22 Purified CD4 1 T cells were further prepared by means of positive selection with anti-CD4 microbeads and MACS (Miltenyi Biotec, Auburn, Calif). The CD4 1 T-cell population obtained in this manner contained less than 0.1% esterase-positive cells, less than 0.1% NK cells, less than 0.1% CD19 1 cells, and greater than 96% CD4 1 T cells.…”
Section: Cell Preparationmentioning
confidence: 99%
“…It is known that IL-12 and/or IL-18 enhance the expression of IFN-γ in adult MCs (Hirohata, 1999;Mbawuike et al, 1999;Puren et al, 1998). This led us to conclude that live RSV stimulates IFN-α production, which in turn induces suppression of innate cytokine responses in neonate MCs.…”
Section: Discussionmentioning
confidence: 86%